The Reformed Vampire Support Group - Jinks, Catherine 1963- (Allen & Unwin, 2009)
"Modern-day vampires negotiate their existence in suburbia, trying to lead normal lives and stay clean with the help of their support group. A subversive, brilliant and funny book from the creator of Evil Genius and Genius Squad."--Provided by publisher